2018
DOI: 10.14238/pi58.4.2018.151-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-1 and short stature in adolescents with beta-thalassemia major

Abstract: Background The  prevalence  of  short  stature  in  thalassemia  patients ranges from 39.3 to 65%.  The  cause  of short stature is complex  and  still up for debate.  In  Indonesia, data on the  prevalence  and risk  factors  of  short  stature  in  adolescents  with  thalassemia  have been limited. Objective To assess for the prevalence and risk factors of short stature in adolescents with beta-thalassemia major. Methods This cross-sectional study was done from February to March 2017 at the Thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This finding supports the findings of Elizabeth et al (8) and Toumba et al (9) who found that short stature was more common in thalassemia patients.…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports the findings of Elizabeth et al (8) and Toumba et al (9) who found that short stature was more common in thalassemia patients.…”
Section: Discussionsupporting
confidence: 92%
“…3 Elizabeth et al did a study on the correlation between serum ferritin level and growth disorders in children with thalassemia and found that the risk factors of short stature were low Insulin-like growth factor (IGF-1) level and low family income. 12 Similarly Saxena et al did a study on growth retardation in thalassemia major patients and found that thalassemic patients are short, have low rate of growth and BMI and have either delayed or absent pubertal spurt, which is related to low hemoglobin and high ferritin level and sub-optimal iron chelation therapy. 13 In our study, ferritin levels did not statistically correlate with growth retardation.…”
Section: Discussionmentioning
confidence: 99%